2012
DOI: 10.1371/journal.pone.0038233
|View full text |Cite
|
Sign up to set email alerts
|

A Single E627K Mutation in the PB2 Protein of H9N2 Avian Influenza Virus Increases Virulence by Inducing Higher Glucocorticoids (GCs) Level

Abstract: While repeated infection of humans and enhanced replication and transmission in mice has attracted more attention to it, the pathogenesis of H9N2 virus was less known in mice. PB2 residue 627 as the virulent determinant of H5N1 virus is associated with systemic infection and impaired TCR activation, but the impact of this position in H9N2 virus on the host immune response has not been evaluated. In this study, we quantified the cellular immune response to infection in the mouse lung and demonstrate that VK627 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 46 publications
(59 reference statements)
4
48
0
Order By: Relevance
“…The rGDK6 and rGDK6-MA viruses showed pathogenicity levels similar to their wild-type forms. As previous studies demonstrated (28)(29)(30), the PB2(E627K) substitution enhances pathogenicity in mammals, and this was observed PFU of virus died ( Fig. 3B and C).…”
Section: Adaptation Of An H6n6 Influenza Virus In Micesupporting
confidence: 76%
“…The rGDK6 and rGDK6-MA viruses showed pathogenicity levels similar to their wild-type forms. As previous studies demonstrated (28)(29)(30), the PB2(E627K) substitution enhances pathogenicity in mammals, and this was observed PFU of virus died ( Fig. 3B and C).…”
Section: Adaptation Of An H6n6 Influenza Virus In Micesupporting
confidence: 76%
“…It is likely that PB2-E627K contributes to mammalian host adaptation and pathogenicity of Sh2/H7N9. An E627K substitution in the PB2 gene has been identified in many human virus isolates, and a number of studies have shown that this mutation is associated with increased virulence of avian influenza viruses for mammals (611). Although some of the recent H7N9 human isolates still retain 627E, the occurrence of the PB2-D701N mutation in these viruses may compensate as the mammalian host adaptation mutation in these viruses (12, 13).…”
Section: Discussionmentioning
confidence: 99%
“…Trypanosoma cruzi, Plasmodium chaubi) and fungal infections (exemplified by experimental infections with Paracoccidioides brasiliensis and Histoplasma capsulatum) (Savino, 2006). To date, several mechanisms have been implicated in influenza virus infection-induced thymic atrophy, such as interference with T-lymphocyte development, increased levels of glucocorticoids and elevated IFN-c production by innate CD8 + T-cells (Liu et al, 2014;Tian et al, 2012;Vogel et al, 2010).…”
Section: Introductionmentioning
confidence: 99%